Nefarmakološko lajšanje kronične bolečine v križu - Marn-Vukadinović, Duša (Rehabilitacija (Ljubljana), 2010)
Chronic non-specific low back pain is discussed in the light of physical therapy and rehabilitation treatment. Exercise therapy is described as the most helpful for such patients since its effectiveness has already been proven. Manual therapy is sometimes needed to enable exercise. Other conservative modalities are considered as adjunctive treatments rather than primary curative interventions. Physiological effects of different methods arediscussed, and guidelines and evidence of effectiveness are summarised. Rehabilitation treatments like back school and cognitive-behavioural therapy are beneficial for chronic pain patients as monotherapy or as a part of a multidisciplinary pain clinic.
Keywords: bolečina; hrbtenica; rehabilitacija; therapy; vocational rehabilitation; zdravljenje